Analysis Of Maternal Risk Factors For Preterm Birth In Airlangga University Hospital 2017-2018 - Almira Maharani, - (2020)
Background: Preterm birth becomes a global problem due to its high rate of morbidity and mortality. Nowadays, Indonesia is on the 5th place of the highest premature birth rate. This study aims to analyze the maternal risk factor towards preterm birth at Airlangga University Hospital 2017-2018. Methods: This research used observational analytic study and case-control approach to observe 178 medical records at University of Airlangga Hospital in Surabaya. The Population of this study is women that gave a birth preterm and aterm. Univariate analysis was used to observe the association between dependent and independent variable. The significance value is P ≤0.05. Data were analysed by using SPSS. Results :The case sample characteristic is 36% patients have overweight BMI; 62.9% patients have normal/hypotension; 69.7% patients gave a birth male baby; 82% patients have no history of disease; There’s no patient have drugs and subtances abuse (0%). The mothers younger than 20 years and older than 35 years has OR=2.13 (95% CI : 1.106-4.11) to become preterm birth. However, the primiparous women have risk for preterm birth 2.978 folds (95%, CI : 576- 5.625) higher. Conclusions :There was a relationship between maternal age and parity to preterm birth. There is no correlation between maternal education, maternal occupation, hemoglobin levels, history of obstetric complications and multiple pregnancy have towards preterm birth. It is necessary to investigate the risk factors of preterm birth and give particular clinical attention.